PEMBERDAYAAN LEMBAGA ADAT DALAM PROSES PENYELESAIAN KONFLIK MASYARAKAT DESA RINDU HATI BENGKULU TENGAH - Herlambang Herlambang; Yagie Sagita Putra; Zico Junius Fernando (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2022)
Abstract: Rindu Hati Village is one of the "old" villages located in Taba Penanjung District, Central Bengkulu Regency, Bengkulu Province. Most of the villagers come from the Rejang Tribe, who highly value the traditions and norms that live in the village community as a habit that will maintain the peace of the village community. Recognition and protection of the rights of community members is carried out by upholding customary law. Actions that can disturb the peace and tranquility of the Rindu Hati village community are violations of customary law norms that have been established by Kutei and disputes, conflicts regarding body and life, property, decency and the sustainability of the natural environment around the village. If there is a conflict that disturbs the balance in the community, then the Village Head, Hamlet Head, Chair or Member of the Customary Deliberation Board, in a "Kutei Customary Deliberation" which is also attended by the Chair/Member of the Village Consultative Body and Syara' Devices are obliged to resolve the conflict. The implementation of service activities is carried out in 3 months with several stages, namely (1) Situation and Needs Analysis, (2) Deliberation with Traditional Leaders and Village Government Apparatuses (3) Formation of the Kutei Customary Deliberation Manuscript (4) Signing of the Kutei Traditional Deliberation Process Manuscript. For each activity, an activity report will be made to LPPM. The final target expected from this service activity is the implementation of the Kutei Customary Law Enforcement in Rindu Hati Village so as to create order and security for the Village community.Keywords: Adat Institution; Community Conflict; Rindu Hati Village.